A review on upcycling as a strategic marketing tool for sustainability in the fashion industry - Emmanuel Abankwah Ofori; Bernice Djangmah Akweley; Benjamin Eghan; Raphael Kanyire Seidu; Richard Acquaye (Journal of Responsible Production and Consumption, 2025)
Purpose – The purpose of this study is to present a mini-integrated review on upcycling as a marketing strategy used by brands in promoting sustainability. Upcycling has emerged as a promising strategy for sustainability in the fashion industry. Activities within the industry have resulted in the release of toxic chemicals, carbon emissions and unsustainable products with significant environmental impacts. This has influenced manufacturers and researchers to adopt alternative but sustainable approaches. Design/methodology/approach – In this mini-integrated review, relevant documents and information were sourced from appropriate databases and websites to provide a brief insight into upcycling as a marketing tool. Findings – This mini-integrated review further provides insight into how effective upcycling can be integrated into a brand’s marketing strategy as a tool to communicate its commitment to sustainability and the production of high-value products for consumer satisfaction. It concludes that the fashion industry has a significant impact on the environment, and the practice of upcycling has surfaced as a potential solution to address issues of sustainability paving the way for further studies. Originality/value – Brands use upcycling to differentiate themselves from competitors and appeal to consumers who prioritize sustainability. By emphasizing the environmental benefits of upcycling, brands can position themselves as leaders in the domain of sustainable fashion practices.